Former Hieromonk Iliodor (Trufanov) in the Plans of the All-Russian Extraordinary Commission to Split the Ranks of the Russian Orthodox Church (1919-1921) - Mikhail Yu. Krapivin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
Introduction. The paper is devoted to the issues of cooperation in 1919-1922 between the Soviet State security agencies and scandalous representative of the extreme right wing of the Orthodox clergy, former hieromonk Iliodor (S. M. Trufanov). Analysis of this plot will help supplement our ideas about the policy of the Soviet State in the religious issue during the Civil War. Materials and methods. The paper is based mainly on the unpublished documents stored in the Central Archive of the Federal Security Service of Russia and in the State Archives of the Volgograd Region. The system of research procedures used in the published work, based on historical-genetic, historical-systemic and concrete historical methods, enabled the author to convincingly reconstruct the plans of the сhekists towards Iliodor. Analysis. In the autumn of 1919, it became obvious to the country’s leadership that it would not be possible to ensure victory on the anti-religious front without direct interference by the All-Russian Extraordinary Commission (hereinafter – the Cheka) in the personnel policy of the Orthodox Russian Church. The variants of promotion to the leading church posts of those hierarchs who were ready to cooperate with the chekists were discussed. Results. Thus, the Soviet State sought to achieve the transformation of the Church into an institution controlled from the outside. However, in the future the Bolsheviks were not needed by Church, neither in the old nor in the updated form. That is why the Cheka intended to use Iliodor to destroy the unity of the ranks of the Orthodox Russian Church, but was not ready (even for the sake of achieving this goal) to seriously support his proposals to the creation of a “renewed people’s church” and to the organization of a broad network of religious communes.